THE IMPROVEMENT OF MATHEMATICAL ABILITY THROUGH CARTESIAR COORDINATE BOARD MEDIA ON GEOMETRY MATERIAL - Dwi Kusuma, Rita; Kurniawati, Naning; Ariful Fathoni, M. Ivan (FKIP Universitas Muhammadiyah Tangerang, 2025)
Education is an important part of life through this means of transformation, including mathematics. Mathematics plays an important role in learning and is part of other sciences. However, students often have difficulty remembering and applying mathematical formulas correctly. This study aims to improve the mathematical ability of VIII grade junior high school students on geometry material using cartesian coordinate board media. The research approach used is experimental method with pretest-posttest control group design. The research subjects consisted of two randomly selected classes, one class as an experimental group using cartesian coordinate board media and one class as a control group using conventional methods. Data were collected through mathematical ability tests given before and after treatment, as well as through observations and interviews. The results showed that the use of cartesian coordinate board media significantly improved students' mathematical abilities on geometry material compared to conventional methods. This improvement can be seen from the comparison of pretest and posttest scores which show a greater improvement in the experimental group. In addition, students showed higher interest and motivation in learning geometry by using this media. From the results of this study it can be concluded that the cartesian coordinate board media is effective in improving students' mathematical abilities in geometry material in class VIII junior high school. Therefore, it is recommended that math teachers consider using this media in the learning process to improve student learning outcomes.